Diseño de un centro comercial para promover el desarrollo económico y comercial en Tulcán - Gordón Rivera, Estefany Madelaine (2023)
The economic challenges faced by the city of Tulcán, exacerbated by the devaluation of the Colombian peso and further worsened by the global economic recession and the pandemic, demand urgent attention and innovative solutions. This thesis focuses on the design of a shopping center as a catalyst for economic and commercial development in Tulcán. The city's strong dependence on cross-border trade leaves it vulnerable to external economic fluctuations, requiring diversification to achieve stability. Analyzing the current situation, it is clear that Tulcán lacks economic diversity, making it susceptible to economic crises. This research proposes the implementation of strategies to stimulate the local economy and tourism, emphasizing the need for diversified economic offerings to attract both local residents and regional tourists, creating employment opportunities for the community. According to (Valdivia, 2016), 'Commercial activity has become an engine that defines the configuration of regions and their cities regardless of their physical magnitude. The economic flows of each town must generate business alternatives for greater private sector participation that allows economic growth and sustainable development, balancing the responsibilities of the public and private sectors.' In the context of this proposal, it is crucial to highlight that the creation of a shopping center not only aims to alleviate Tulcán's economic challenges but also to improve the quality of life for its residents. The inclusion of accessible public spaces, green areas, and recreational zones within the architectural design will not only enrich the commercial offerings but also contribute to the overall well-being of the community. This holistic approach recognizes the interconnectedness between economic development and collective well-being, aspiring to create an urban environment that is not only prosperous commercially but also habitable and enriching for all residents. As per (Riveros, 2016), 'The mall is a symbol of economic development and progress for many sectors of the population. For a municipality, its arrival becomes highly relevant due to the strong attracting power it brings, along with a revitalization of local commerce.